IDENTIFIKASI KAWASAN PELUANG PEMENUHAN TARGET RUANG TERBUKA HIJAU 30% DI DKI JAKARTA - Susi Andriani; Tarsoen Waryono; Mohammad Hasroel Thayib (Environmental Research Center (PPLH) of Udayana University, 2014)
The research was conducted on 3 components of Green Open Space (GOS) in Jakarta,namely landscaping, agriculture and forestry. The research objective was to determine thedistribution and extensive of Existing Green Open Space in Jakarta in 2012, and to identifythe potential opportunity areas to fulfill the target of 30% GOS in Jakarta. Searchdistribution is done with Landsat TM imagery aids Band 54 corrected in 2011 by analyzingthe vegetation index values (NDVI). Search area opportunity to meet the target of 30% wasthe buffer zone (river banks, beaches and water tanks), as well as the areas that haveawakened to meet the obligation Law. 26 of 2007. The results showed the existing greenopen space in Jakarta in 2012 was 7,842.61 ha (13.27%) of the total land area of Jakarta.realization Landscaping recorded 2,718.37 ha, 1,950.08 ha Forestry, and Agriculture2,813.29 ha . The opportunity potential areas to fulfill the target recorded more of 10,003.92ha.